Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Loyalitas Pasien Dengan Kepuasan Pasien Sebagai Variabel Intervening (Studi Pada Poliklinik Jantung RSUD Bakti Dharma Husada Surabaya) - Matheous Tamonsang; Muhammad Dwi Apriliyanto (PRAGMATIS, 2020)
The purpose of this study was to determine the effect of service quality and facilities on patient loyalty at the Heart Clinic at Bhakti Dharma Husada Hospital Surabaya with patient satisfaction as a moderating variable. In this study, sampling was carried out by non-probability sampling with a purposive sampling procedure, which means that the sampling technique is based on certain considerations. With a total sample of 82 people. Research data processing using data analysis respondents using path analysis (path analysis) with the help of SPSS 16. The results concluded that service quality has a significant effect on patient satisfaction, facilities have a significant effect on patient satisfaction, service quality partially has a significant effect on patient loyalty, facilities are Partial significant effect on patient loyalty, patient satisfaction partially significant effect on patient loyalty, patient satisfaction is not an intervening variable service quality and facilities variables on patient loyalty.